N-acetyltransferase (nat) is a critical conjunct of photoperiodism between the circadian system and endocrine axis in Antheraea pernyi. - Ahmed A M Mohamed (Public Library of Science (PLoS), 2014)
Since its discovery in 1923, the biology of photoperiodism remains a mystery in many ways. We sought the link connecting the circadian system to an endocrine switch, using Antheraea pernyi. PER-, CLK- and CYC-ir were co-expressed in two pairs of dorsolateral neurons of the protocerebrum, suggesting that these are the circadian neurons that also express melatonin-, NAT- and HIOMT-ir. The results suggest that a melatonin pathway is present in the circadian neurons. Melatonin receptor (MT2 or MEL-1B-R)-ir in PTTH-ir neurons juxtaposing clock neurons suggests that melatonin gates PTTH release. RIA showed a melatonin rhythm with a peak four hours after lights off in adult brain both under LD16:8 (LD) and LD12:12 (SD), and both the peak and the baseline levels were higher under LD than SD, suggesting a photoperiodic influence. When pupae in diapause were exposed to 10 cycles of LD, or stored at 4 °C for 4 months under constant darkness, an increase of NAT activity was observed when PTTH released ecdysone. DNA sequence upstream of nat contained E-boxes to which CYC/CLK could bind, and nat transcription was turned off by clk or cyc dsRNA. dsRNA(NAT) caused dysfunction of photoperiodism. dsRNA(PER) upregulated nat transcription as anticipated, based on findings in the Drosophila melanogaster circadian system. Transcription of nat, cyc and clk peaked at ZT12. RIA showed that dsRNA(NAT) decreased melatonin while dsRNA(PER) increased melatonin. Thus nat, a clock controlled gene, is the critical link between the circadian clock and endocrine switch. MT-binding may release PTTH, resulting in termination of diapause. This study thus examined all of the basic functional units from the clock: a photoperiodic counter as an accumulator of mRNA(NAT), to endocrine switch for photoperiodism in A. pernyi showing this system is self-complete without additional device especially for photoperiodism.